Avaliação de alternativas para geração de energia elétrica a partir de resíduos sólidos urbanos - Gehm, Sandi da Costa (2019)
Solid waste management is a major problem in most developing countries, as MSW generation is gradual and is associated with intense industrial activity and population growth. The decomposition of organic matter promotes the release of biogas, whose main constituents are carbon dioxide and methane, is a greenhouse gas whose emission causes global warming, besides generating unpleasant odors and offering risks to the population. Thus, the generation of energy from municipal solid waste has been presented as a possible alternative, with a view to sustainable development. In this context, this paper aims to evaluate the technical and economic aspects of power generation from urban solid waste, through a comparative study between power generation in landfills using biogas and its burning in incineration plants. To this end, a case study was conducted considering the municipality of Ijuí, located in the northwest of the state of Rio Grande do Sul, with a population of 87 thousand inhabitants, subsequently using the methodology proposed by the National Center for Biomass Reference and by Polleto to determine the power and energy to be generated through biogas and incineration respectively and thereafter perform the economic analysis using the Abrelpe, CAPEX and OPEX parameters for the biogas energy utilization while the incineration analysis was performed. based on the study by Stubenvoll. The results showed that from an energy point of view, the incineration plant starts generating substantial energy as early as the first year, but that economically generating energy through biogas is more viable due to the low investment and operating costs. Thus, through the results obtained it can be noted that the generation and use of electricity from local sources can contribute to strategic actions in the municipalities.